Occupational Licensing and Maternal Health: Evidence from Early Midwifery Laws - Anderson, D. Mark; Brown, Ryan; Charles, Kerwin Kofi; Rees, Daniel I. (Journal of Political Economy, 2020)
Exploiting variation across states and municipalities in the timing and details of midwifery laws introduced during the period 1900–1940 and using data assembled from various primary sources, we find that requiring midwives to be licensed reduced maternal mortality by 7%–8% and may have led to modest reductions in infant mortality. These estimates represent the strongest evidence to date that licensing restrictions can improve the health of consumers and are directly relevant to ongoing policy debates on the merits of licensing midwives.